Transport and regulatory mechanisms of boron in plants - Zhou, Dan; Luo, Rui; Ma, Bojun; Chen, Xifeng (Frontiers in Plant Science, 2025)
Boron (B) is a vital micronutrient necessary for the proper development of plants. However, B exhibits a very narrow concentration range between deficiency and toxicity in plants, making precise regulatory control over its uptake, translocation, and cellular efflux critical for maintaining overall B homeostasis. Genetic analyses of Arabidopsis thaliana show that boron uptake and translocation are mediated by two families of transmembrane transporter proteins: NIPs (nodulin-26-like intrinsic proteins), which facilitate the permeation of boric acid, and BORs, responsible for exporting borate from cells. Importantly, the identification and characterization of NIPs and BORs have been essential for elucidating B homeostasis and its physiological roles not only in Arabidopsis but also in diverse plant species. Furthermore, the homeostasis of B is maintained by multi-level regulation of its transport proteins, including transcriptional modulation, mRNA stability, translational repression, and endocytic degradation. Moreover, modulating B transport gene expression to enhance tolerance to B deficiency or toxicity can improve plant growth under unfavorable B nutrient conditions. Therefore, generating B-efficient or B-tolerant plants is a cost-effective and sustainable agricultural strategy. In this review, we discuss the physiological roles of B transport proteins and their regulatory mechanisms, focusing on intracellular localization and abundance.